1989
DOI: 10.1037/0735-7028.20.3.153
|View full text |Cite
|
Sign up to set email alerts
|

The distressed psychologist: Prevalence and treatment considerations.

Abstract: Investigated the level and types of distress in a sample of 379 psychologists, using survey methodology. Overall, Ss were healthy and satisfied with work and interpersonal relationships. 10% of Ss experienced distress in the areas of depression, marital/relationship, physical illness, alcohol use, and loneliness. A distress band was calculated and ranged from 9% for multiple categories to 19% for single categories of distress. A subsample of Ss in distress from alcohol use were characterized by use of controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 25 publications
6
70
0
1
Order By: Relevance
“…Strained or terminated relationships, personal caring roles, and work‐related factors were widely shared experiences, highlighting the multiplicity of stressors, echoing previous findings (Cushway & Tyler, 1995; Deutch, 1984; Farber, 1983; Gilroy et al , 2002; Guy, 1987; Guy et al , 1989; Hellman, Morrison, & Abramowitz, 1987; Nash, Norcross, & Prochaska, 1984; Thoreson et al , 1989). Work stressors were specifically associated with high‐pressure, long hours, and organizational expectations, and, for some, professional doubt.…”
Section: Discussionsupporting
confidence: 75%
“…Strained or terminated relationships, personal caring roles, and work‐related factors were widely shared experiences, highlighting the multiplicity of stressors, echoing previous findings (Cushway & Tyler, 1995; Deutch, 1984; Farber, 1983; Gilroy et al , 2002; Guy, 1987; Guy et al , 1989; Hellman, Morrison, & Abramowitz, 1987; Nash, Norcross, & Prochaska, 1984; Thoreson et al , 1989). Work stressors were specifically associated with high‐pressure, long hours, and organizational expectations, and, for some, professional doubt.…”
Section: Discussionsupporting
confidence: 75%
“…Research has shown that professional psychologists are aware of the ethical issues surrounding impairment among their colleagues (Thoreson et al, 1989). The literature on graduate student impairment also notes that graduate students are aware of peers' problematic or impaired behavior.…”
Section: Identifying Impairment In Graduate Studentsmentioning
confidence: 98%
“…In a review of the literature on the psychological adaptation of psychologists, Sherman (1996Sherman ( ) con-1997Cushway, et al, 1996;Good et al,1995;Guy et al, 1989;Pope and Tabachnick, 1994;Schwebel and Coster, 1998;Sherman and Thelan, 1998;Thoreson et al, 1989). Further research on the psychological adaptation of clinical psychologists is important for several reasons.…”
Section: Introductionmentioning
confidence: 99%